Great migrations : whales, wildebeests, butterflies, elephants, and other amazing animals on the move - Carney, Elizabeth, 1981- (Washington, D.C. : National Geographic, 2010)
An illustrated guide to animal migrations around the world, tracing the paths of wildebeests, whales, butterflies, elephants, and other animals as they travel long distances.
"National Geographic Kids."
Includes index.
6.6
3-6
Keywords: Animal migration -- Juvenile literature; Migratory animals -- Juvenile literature; Animal migration; Migratory animals; Animals -- Migration; Migratory animals